Product Marketing and Small Business Research, 2006–2026: Growth and Collaboration Fragmentation - Riefky Prabowo (Yayasan Lentera Avanya Nagari, 2026)
This study maps the development of product marketing and small business research between 2006 and 2026. While previous studies focused on specific topics like market orientation or digital adoption, this research examines how the field has evolved as an intellectual landscape. Using a bibliometric approach with Bibliometrix and VOSviewer, the study analyzed 886 Scopus-indexed articles selected from an initial 1,799 papers within the Business, Management, and Accounting subject area. The findings reveal that publication activity became more sustained after the mid-2010s. Keyword analysis shows the field is strongly anchored in marketing (126 appearances), followed by innovation (76), marketing strategy (49), and SMEs (49). Citation analysis indicates concentrated intellectual influence, led by the United Kingdom (1,694 citations), the United States (1,436), and Italy (1,313). Thematic mapping identifies commerce, small business, and sales as motor themes, while marketing, marketing strategy, and entrepreneurship serve as basic themes. Furthermore, the co-authorship network reveals fragmented collaboration across small author clusters. Ultimately, this study clarifies the growth, thematic structure, and collaboration patterns of the field, helping scholars and practitioners identify established themes, emerging digital topics, and future opportunities.